If you were an adjective - Dahl, Michael; Gray, Sara Jean (Minneapolis, Minn. : Picture Window Books, 2006)
Discover the colorful, brilliant, dazzling life of an adjective! In this imaginative picture book, young grammarians are introduced to these busy words that describe nouns. Along with bright illustrations and colorful fonts, bestselling author Michael Dahl (If You Were a Verb and If You Were a Noun) delivers an imaginative read-aloud for your littlest grammarians.
L0540
Keywords: English language -- Adjective